(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Marriage in India is nearly universal, traditionallyendogamous in terms of caste, monogamous for both legal and social reasons, andmost commonly arranged by the parents or close relatives of the bride and groom(e.g., Harrell 1997; Srinivas 1984; Uberoi 1994). Weddings are lavish socialoccasions, usually paid for by the family of the bride, and may entail asignificant transfer of wealth from the family of the bride to the bride, thegroom, or the groom’s family referred to as dowry.